Taylor swift: 1989 - the ultimate fan guide emagazine (Taylor Swift: 1989 - The Ultimate Fan Guide.)
By 2014, Taylor Swift was already at the top of her game, with the chart-topping achievements of her albums Fearless, Speak Now and Red. She'd brought country music to a new generation of listeners, but she aspired to do even more—something different that would take her music to another level. That desire resulted in Swift's fourth No. 1 album, and it transformed her from a country princess into a bona fide pop superstar. With catchy hooks, playful lyrics and a dreamy, late-’80s synth-pop sound running throughout, the album was a critical and commercial success, selling 1.28 million copies in its first week and winning Swift her second album of the year Grammy. Later, the release of 1989 (Taylor's Version) in 2023 landed the singer her 13th No. 1 on the Billboard 200. As the original album celebrates its 10th anniversary, this book looks back on how it changed the pop landscape and the trajectory of Taylor Swift’s career. This is the story of 1989.